Daya terima dan kandungan gizi formulasi biskuit IBBU sebagai pangan darurat bencana pereda stres ibu hamil - Salma Chalisha; Annis Catur Adi (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Disasters can cause emergencies that have the potential to impact food and nutrition crises, especially in the first five days (first phase of emergency response); therefore, assistance is needed in the form of providing food immediately. Pregnant women are vulnerable groups that can become victims of disasters. Insufficient intake by pregnant women during a disaster can lead to a potential incidence of infection, stunting, and malnutrition in infants. Additionally, disaster conditions can cause pregnant women to experience stress.Objectives: This study aimed to analyze the formulation of disaster emergency food biscuits in an effort to relieve stress in pregnant women victims of disasters.Methods: This type of research was purely experimental on the biscuit formula and had a completely randomized design with five formulas. The nutritional content was calculated using DKBM. The acceptability test at the organoleptic stage was quasi-experimental. The organoleptic quality tested on 3 limited panelists and 25 somewhat trained panelists was analyzed using the Kruskal Wallis test (α ≤ 0,05). Results: The results showed that the formula with the best acceptability was F1 (purple sweet potato flour 30 g; skim milk powder 10 g; soy protein isolate 5 g; nutmeg powder 7 g) with total energy per serving  247,4 kcal, which fulfills 11% of the energy needs of pregnant women. Giving 7 grams of nutmeg powder can potentially relieve stress in pregnant women if consumed one serving per day for 15 days.Conclusion:  An increasing number of substitutions resulted in lower acceptability and higher energy, protein, and fiber contents in biscuits. In addition, biscuits are produced with high nutritional content and can relieve stress. The formula with the best acceptability was obtained using F1 (7,5% purple sweet potato flour, 2,5% skim milk powder, 1,3% soy protein isolate, and 1,8% nutmeg) and had the potential to relieve the stress of pregnant female victims of the disaster.